2019
DOI: 10.1002/app.48510
|View full text |Cite
|
Sign up to set email alerts
|

A simple and effective approach to produce tubular polysaccharide‐based hydrogel scaffolds

Abstract: The production of porous tubular scaffolds is of great interest in the field of tissue engineering, given the existence of several tubular structures in the human body. In this work, a methodology was developed for the fabrication of tubular‐shaped scaffolds based on the casting of polymeric solutions by controlled crosslinking mediated by a semipermeable cast. The fabrication of hydrogel tubular scaffolds from chitosan–pectin polymeric mixtures (tCh‐P, 3% w/v) was performed to attest the feasibility of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Here, the compression test was used to evaluate the mechanical properties of hydrogels. We found a direct proportionality between hydrogel stiffness and polymer concentration, with relatively low Young's modulus (E) (1-4 kPa), in close agreement with the behavior and values reported for chitosan hydrogels (0.5-1.5 kPa) (Shitrit et al, 2019) and Ch-Pec scaffolds (2 kPa) (Bombaldi de Souza et al, 2020), and comparable to those of the ECM of healthy biological tissues (0.1-1 kPa) (Wang et al, 2014). Furthermore, there were no significant differences between the − DMEM and +DMEM hydrogel, indicating that the amount of DMEM introduced into the system to deliver cells inside the system, is small enough to do not induce any change in the hydrogel mechanical properties.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, the compression test was used to evaluate the mechanical properties of hydrogels. We found a direct proportionality between hydrogel stiffness and polymer concentration, with relatively low Young's modulus (E) (1-4 kPa), in close agreement with the behavior and values reported for chitosan hydrogels (0.5-1.5 kPa) (Shitrit et al, 2019) and Ch-Pec scaffolds (2 kPa) (Bombaldi de Souza et al, 2020), and comparable to those of the ECM of healthy biological tissues (0.1-1 kPa) (Wang et al, 2014). Furthermore, there were no significant differences between the − DMEM and +DMEM hydrogel, indicating that the amount of DMEM introduced into the system to deliver cells inside the system, is small enough to do not induce any change in the hydrogel mechanical properties.…”
Section: Discussionsupporting
confidence: 89%
“…S6), there are no significant differences among the different formulations and, therefore, the porosity was not affected by the percentage of final polymer used in our study, showing mean values in the range of 150-220 μm. This is lower than most Ch-Pec hydrogels (often higher than 350 μm) (Bombaldi de Souza et al, 2020;Tentor et al, 2017), although lower values (from 15 μm to 110 μm) were observed in some Ch-Pec or Ch-only hydrogels (Birch et al, 2015;Boido et al, 2019). Taking into account their swelling ability, with the High and Medium samples swelling less in the first 10 min and being more stable over time compared to the Low formulation, this is likely due to a tightly cross-linked structure and, therefore, to the presence of more compact pores.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, no significant differences were evidenced between the hydrogel formulations with and without the addition of DMEM, indicating that the amount of DMEM introduced into the system to load the cells inside did not induce any change in the mechanical properties of the hydrogel. Our findings are in agreement with those reported by Bombaldi de Souza and colleagues in 2020 [ 44 ], where the elastic modulus of chitosan and pectin tubular scaffolds was lower than 2 kPa in the strain range between 5 and 20%, although this value was measured performing a tensile testing test. Unfortunately, to the best of our knowledge, there are no Ch-Pec systems in the literature characterized by compressive tests.…”
Section: Discussionsupporting
confidence: 94%
“…Next, we progressed to bioprinting circular models using PLMA, such as rings and cylinders since they lack structural pillars that help during standard bioprinting, and due to the existence of many structures like these in the human body, such as vascular and neural tissues. [48,49] Stable rings fully composed of PLMA were obtained when bioprinting multiple passes of 10 layers to generate thicker structures along with simultaneously photocrosslinking ( Figure 5F and Supplementary Video 1 ). When we challenged the system by switching bioprinting multiple passes for bioprinting 10 circumferences in a continuous spiral with a pitch equal to the fiber diameter, the filaments coalesced since the filament size of the whole rings was 1.6 ± 0.3 mm, instead of 578 ± 68 µm of a single layer.…”
Section: Resultsmentioning
confidence: 99%